Analysis Technical of the Use of Ground Water Resources for Rice Plantation Irrigation in Jembrana Regency - Hendrayana S, Angga; Hendrayana S, Sumiyati; Madrini, Ida Ayu Gede Bintang (Jurnal BETA (Biosistem dan Teknik Pertanian), 2018)
The Ground water is one of water resources that can be used to fullfill the needs of irrigation. With the limited availability of water, it is attempted by utilizing ground water using pump wells. The use of pump wells has not been maximal in fulfilling the irrigation water requirement so further research is needed. The objectives of this research are: (1) To know the technical use of groundwater resources for irrigation using pump wells, and (2) to analyze the ability of pump wells in subak samples in Jembrana Regency to irrigation water needs. This research uses descriptive analysis through survey method, taking data using primary and secondary data. Available discharge analysis is obtained through direct survey method of spaciousness and analysis of irrigation water needs carried out with the help of CROPWAT 8.0 software. Based on the irrigation water balance analysis, there is a reduction between the irrigation water demand and the availability of irrigation water to 3 subak samples. In Subak Sari Merta it is known that there is water shortage 2 periods that is the period of June I equal to 171.900 l / day, January I 149.700 l / day. Subak Brawantangi is known that there is water shortage as much as 4 periods that is the period of August I equal to 123.900 l / day , August II 99.200 l / day, March I 98,200 l / day, March II 78.200 l / day. Subak Tegal Badeng is known that there is water shortage for 8 periods that is June II period is 64.000 l / day, June III 178.500 l / day, August III 35.600, September I 35.100 l/day, September II 38.400 l/day, September III 32.900 l/ day, November I 48,400 l / day, November III 149.700 l / day. Water deficit occurs because in the period of the month is done so that the processing of irrigation water needs tend to be high. To be able to meet the needs of irrigation water needed for the processing of the soil, the Subak Sari is done by the turn system using irrigation water so that agricultural activities can run well.